2015
DOI: 10.1037/stl0000018
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotional intelligence in peer instructional dyads.

Abstract: The aim of this study was to empirically examine the experiential process of peer instructional dyads in training students in novice level professional competencies related to supervision (p. 778; Falender et al., 2004). More specifically, this study examined the associations among emotional intelligence (EI), process behaviors, satisfaction, and team performance using a sample of 81 peer instructional dyads in a controlled experimental condition. Findings reveal that the supervised trainees in this sample who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Individuals with high emotional intelligence are better able to accept criticism. Findings related to the workplace suggest that the greater emotional intelligence a supervised trainee has, the better they are able to adapt to various managers (Clarke, 2006;Rieck, Hausdorf, & Callahan, 2015).…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Individuals with high emotional intelligence are better able to accept criticism. Findings related to the workplace suggest that the greater emotional intelligence a supervised trainee has, the better they are able to adapt to various managers (Clarke, 2006;Rieck, Hausdorf, & Callahan, 2015).…”
Section: Emotional Intelligencementioning
confidence: 99%
“…However, the assertion that followership is unimportant has never been validated. The few studies comparing contributions to team outcomes have shown an equal or greater influence of followership (Hoption, 2016; Rieck, Hausdorf, & Callahan, 2015; Sy, Tram, & O’Hara, 2006). Followership also has individual impact: early-career jobs involve greater followership than leadership skills (although see MacKenzie, Podsakoff, & Paine, 1999), the attainment of managerial positions depends on followership (Agho, 2009; Latour & Rast, 2004), and one of the primary causes of executive derailment is poor followership (Gentry & Shanock, 2008; Lombardo, Ruderman, & McCauley, 1988; Van Velsor & Leslie, 1995).…”
mentioning
confidence: 99%